WAKAF BERJANGKA DALAM MAZHAB SYAFI’I DAN MAZHAB MALIKI: ANALISIS KOMPARATIF DAN RELEVANSINYA TERHADAP HUKUM WAKAF DI INDONESIA - Junaidi, Muhammad Teguh; Saifulloh, Kholid (LPPM STAI Muhammadiyah Probolinggo, 2025)
Temporary endowment (wakaf berjangka) is a contemporary form of Islamic endowment that remains a subject of debate in classical Islamic jurisprudence. In Indonesia, this practice has gained legal recognition through Law Number 41 of 2004, despite the fact that the majority of its Muslim population follows the Shafi’i school, which rejects the concept. This study aims to analyze the perspectives of the Shafi’i and Maliki schools regarding temporary endowment and assess its relevance to Indonesia’s endowment law. The research employs a library research method with a normative-comparative approach, examining textual evidences, legal maxims, and scholarly opinions from both schools. The findings reveal that the Shafi’i school prohibits temporary endowments due to its requirement of perpetuity as a condition for validity. Conversely, the Maliki school allows it, offering a more flexible interpretation. In the context of Indonesian positive law, the Maliki view is deemed more applicable and relevant. The study recommends further empirical research on the practice of temporary endowment in Indonesia and comparative analysis with other schools, such as Hanafi and Hanbali, to enrich the development of adaptive and contextual endowment law.